The Oxford handbook of European history, 1914-1945 - Doumanis, Nicholas 1964- HerausgeberIn; Oxford University Press (Oxford University Press, 2016)
Introduction : Europe's age of catastrophe in context / Nicholas Doumanis -- Belle époque : Europe before 1914 / Alan Sked -- Societies at war, 1914-1918 / Stefan Goebel -- Total war : family, community, and identity during the First World War / Tammy M. Proctor -- The left and the revolutions / David Priestland -- The economics of total war and reconstruction, 1914-1922 / Matthias Blum and Jari Eloranta -- The new diplomacy and the new Europe, 1916-1922 / Alan Sharp -- Nation states, minorities, and refugees, 1914-1923 / Ryan Gingeras -- Remaking Europe after the First World War / Conan Fischer -- The Great Depression in Europe / Roger Middleton -- 'A low dishonest decade'? War and peace in the 1930s / Anthony Adamthwaite -- Interwar crises and Europe's unfinished empires / Matthew G. Stanard -- Rural society in crisis / Laird Boswell -- Interwar democracy and the League of Nations / Andrea Orzoff -- The political 'left' in the interwar period, 1924-1939 / Pamela Radcliff -- Fascism and the right in interwar Europe : interaction, entanglement, hybridity / Aristotle Kallis -- Social policy, welfare, and social identities, 1900-1950 / Julia Moses -- Discipline, terror, and the state / Paul M. Hagenloh -- The nationalization of the masses / Roger D. Markwick and Nicholas Doumanis -- Political violence and mass society : a European civil war? / Mary Vincent -- European sexualities in the age of total war / Dagmar Herzog -- 'America' and Europe, 1914-1945 / David W. Ellwood -- European integration, human rights, and romantic internationalism / Marco Duranti -- Wartime economies, 1939-1945 : large and small European states at war / Jeremy Land and Jari Eloranta -- Axis imperialism in the Second World War / Shelley Baranowski -- Everyday life in wartime Europe / Christoph Mick -- The Holocaust in European history / Mark Roseman -- Europe's civil wars, 1941-1949 / Aviel Roshwald -- Nation-building and moving people / Alexander V. Prusin -- Europe, the war, and the colonial world / Martin Thomas -- Power relations during the transition from Nazi to post-Nazi rule / Gareth Pritchard -- The memory of Europe's age of catastrophe, 1914-2014 / Ben Mercer